Enterokinase deficiency associated with novel TMPRSS15 gene mutations: a case report - Li, Yunxi; Li, Ruijuan; Pan, Yanyan; Zhou, Weiran; Wang, Xingcui; Dong, Linlin; Liu, Xuemei; Zhang, Hongxia (Frontiers in Pediatrics, 2025)
BackgroundEnterokinase deficiency (EKD,OMIM #226200) is a rare autosomal recessive genetic disorder caused by mutations in transmembrane protease serine 15 (TMPRSS15). Herein, we report a case of EKD in a patient with novel compound heterozygous TMPRSS15 mutations.Case presentationA 2-month-old female infant presented with chronic diarrhea, vomiting, pallor, general edema, skin lesions, and a failure to gain weight. Further examination revealed anemia, hypoalbuminemia, and multiorgan damage. Whole-exome sequencing further revealed two novel heterozygous variants of TMPRSS15: c.2611C>T (p.Arg871Ter) and c.1584_1585insCTTT (p.Glu529LeufsTer2). The clinical symptoms dramatically improved following pancreatic enzyme replacement. During a one-year follow-up, the patient showed a normal rate of physical development, with no recurrence of anemia, hypoproteinemia, coagulopathy or skin lesions.ConclusionHerein, we presented a clinical case of EKD with two novel compound heterozygous mutations in TMPRSS15 who achieved dramatic symptom improvements following pancreatic enzyme supplementation. This case enriches the genotypic spectrum of EKD and provides a reference for the diagnosis and treatment of similar cases. This case suggests that if zymogen activation testing is not possible, genetic analysis may be an effective tool to facilitate early diagnosis. Further, early pancreatic enzyme supplementation is a clinical strategy which can achieve satisfactory outcomes.